2009
DOI: 10.1007/978-3-642-04636-0_47
|View full text |Cite
|
Sign up to set email alerts
|

CAMera for PLE

Abstract: Successful self-regulated learning in a personalized learning environment (PLE) requires self-monitoring of the learner and reflection of learning behaviour. We introduce a tool called CAMera for monitoring and reporting on learning behaviour and thus for supporting learning reflection. The tool collects usage metadata from diverse application programs, stores these metadata as Contextualized Attention Metadata (CAM) and makes them accessible to the learner for recapitulating her learning activities. Usage met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…on learning resources, communities, groups, etc. The ODS data complies with the CAM (Context Automated Metadata) format [14], which provides a standard metadata specification for collecting and storing social data. A CAM schema aims to store whatever has attracted users' attention while the users are working with the platform.…”
Section: Datamentioning
confidence: 99%
“…on learning resources, communities, groups, etc. The ODS data complies with the CAM (Context Automated Metadata) format [14], which provides a standard metadata specification for collecting and storing social data. A CAM schema aims to store whatever has attracted users' attention while the users are working with the platform.…”
Section: Datamentioning
confidence: 99%
“…Being aware of one's own activities is a prerequisite for reflection. In [2], we have shown that one way of helping a learner to become aware of his actions and learning processes is to record and store his interaction with his computer and to then analyse the collected data. Results of these analyses can on the one hand be used to foster his self-reflection processes or on the other hand to give recommendations, e.g.…”
Section: User Monitoring and Learning Analyticsmentioning
confidence: 99%
“…In the field of Technology Enhanced Learning, monitoring student activity has been proposed as a tool for promoting self-reflection [10,22], awareness [10,14], student assessment [14], course management [15], course evaluation [25], and, of course, learning adaptation and personalization [26], among other potential applications.…”
Section: Related Workmentioning
confidence: 99%